Pierwsze lata Archiwum Uniwersytetu Kardynała Stefana Wyszyńskiego w Warszawie - organizacja i funkcjonowanie - Milewski, Dariusz (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The article is devoted to the creation and the first period of activity of archive of the Cardinal Stefan Wyszyński University in Warsaw. The Catholic Academy in Warsaw archived its documenta- tion in particular registry offices. The change took place with the creation of the Archive of UKSW in 2000. The article describes the circumstances of the creation of the Archive and its legał founda- tion. It also presents the development of the position of the Archive in the university structure in view of university legał acts and practice. The current activity of the archives is also discussed, the causes of the initial problems are analysed and the development perspective is indicated.